2021
DOI: 10.1007/s00158-021-02969-1
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on stress-based fail-safe topology optimization and multiple load path design

Abstract: Explicitly considering fail-safety within design optimization is computationally very expensive, since every possible failure has to be considered. This requires solving one finite element model per failure and iteration. In topology optimization, one cannot identify potentially failing structural members at the beginning of the optimization. Hence, a generic failure shape is applied to every possible location inside the design domain. In the current paper, the maximum stress is considered as optimization obje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Hederberg et al [14] used moving morphable components (MMCs) to simulate structural damage and combined with density-based topology optimization method to obtain damage-safety design. Kranz et al [15] used the maximum length scale method to conduct a damage-safety topology optimization study with the goal of stress minimization. During the optimization process, they evaluated the failure scenarios according to the actual load path, and not only designed the damage-safety design with good performance, but also reduced the calculated cost.…”
Section: Introductionmentioning
confidence: 99%
“…Hederberg et al [14] used moving morphable components (MMCs) to simulate structural damage and combined with density-based topology optimization method to obtain damage-safety design. Kranz et al [15] used the maximum length scale method to conduct a damage-safety topology optimization study with the goal of stress minimization. During the optimization process, they evaluated the failure scenarios according to the actual load path, and not only designed the damage-safety design with good performance, but also reduced the calculated cost.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the methodology was significantly more efficient than densitybased techniques, since the number of analyses required is proportional to the number of geometric components and independent from the mesh. Kranz et al [26] proposed load-path-based evaluation scheme for fail-safe topology optimization, where redundant structures are obtained at much less computational cost. Hederberg and Thore [23] combined density-based topology optimization with a moving morphable component representation of structural damage, obtaining more robust fail-safe designs.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been applied to design porous shell structures (Träff et al, 2021). Other notable extensions include the design of porous structures with gradation in the porosity and pore size (Schmidt et al, 2019;Das and Sutradhar, 2020), use of multiple materials (Li et al, 2020;Zhao and Zhang, 2021), stress constraints (Kranz et al, 2021), as well as design of self-supporting infill (Liu et al, 2021) and fiber-reinforced structures (Li et al, 2021). Dou proposed a projection operator to implicitly incorporate local volume constraints (Dou, 2020).…”
Section: Introductionmentioning
confidence: 99%